2020
DOI: 10.1007/s00107-020-01611-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of wood distillate from residual virgin chestnut biomass

Abstract: The antibacterial properties of a wood distillate obtained from residual virgin chestnut biomass were investigated by means of quantitative MIC (minimum inhibitory concentration) test and a whole-cell assay that specifically responds to different classes of antimicrobials on the basis of the mode of action. Results indicate that wood distillate is active against gram-positive and gram-negative bacteria related to human and/or fish diseases with a mechanism, which could mainly affect wall components and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…On the other hand, the Ag + on the surface of wood@Ag@SA had a strong oxidation capacity, which could destroy the protein, lipid, and DNA of the cell through the catalytic effect of the cell enzyme, so that the cell produced metabolic disorders, thus losing activity. The silver ions on the surface of wood@Ag@SA could also bind with enzymes in donor sulfhydryl groups to release other ions in the cell, thus making it difficult for cellular enzymes to play their roles and causing bacterial inactivation [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Ag + on the surface of wood@Ag@SA had a strong oxidation capacity, which could destroy the protein, lipid, and DNA of the cell through the catalytic effect of the cell enzyme, so that the cell produced metabolic disorders, thus losing activity. The silver ions on the surface of wood@Ag@SA could also bind with enzymes in donor sulfhydryl groups to release other ions in the cell, thus making it difficult for cellular enzymes to play their roles and causing bacterial inactivation [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such effectiveness was demonstrated when WD was applied at a concentration of 10%, whereas more diluted concentrations were less effective for the devitalization of P. muralis, although this lichen species has somewhat been recognized as less resistant to biocide treatments than others (Favero-Longo et al, 2017). A 10% WD treatment has been shown to have an inhibition effect against insects and some gram-positive bacteria (Lee et al, 2010;Mmojieje and Hornung, 2015), but other laboratory studies showed that even lower concentrations of 1-2% may be sufficient to inhibit the growth of some fungi and bacteria (Jung, 2007;Lee et al, 2010;Misuri and Marri, 2021). With this regard, the poor sensitivity of P. muralis to 5% and lower WD concentrations may depend on a higher resistance of saxicolous lichens with respect to other (micro-)organisms, but also on the fact that our experiments were run in the field under real conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Different wood distillate concentrations (0.50%, 0.75%, 1%, 5%, 10%), selected with reference to the range of effectiveness reported against other biological targets (e.g. Mmojieje and Hornung, 2015;Misuri and Marri, 2021), were applied with a cellulose poultice (Arbocel BC 1000, JR Pharma, Rosenberg, Germany), approx. 1 cm thick, containing ca.…”
Section: Wood Distillate and Biocides Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chestnut shells contain various phenolic compounds [3], and the tough skin contains a large amount of tannins [4], which show antioxidant [3,5,6], fat absorption-inhibiting [7], and anti-adipogenic activities. Tannins also reportedly have preventive effects against heart disease [8], diabetes [9], and cancer [10], as well as antibacterial [11,12] and deodorizing properties [13]; therefore, the utilization of fruit peels is considered important from an industrial perspective [14]. However, the existing Japanese varieties of chestnuts are difficult to peel, and the bioactivity of the inner bark of trees have not been investigated.…”
Section: Introductionmentioning
confidence: 99%